Experimental and numerical evaluation of force transduced by interactive fiber rubber composite structures - Annadata, Achyuth Ram; Lohse, Felix; Gereke, Thomas; Cherif, Chokri (Wydawnictwo Politechniki Łódzkiej, 2022)
Shape memory alloys (SMA) represent a category of smart materials and are widely used as actuators for many applications ranging from aircraft-automotive as vibration dampers to medical stents mainly because of their high energy density and their ability to generate high actuating forces. One of the potential applications of use of SMA is in robotics. SMA integrated composites provide a light-weight solution for conventional grippers but have their fair share of disadvantages such as minimal movements due to constrained degrees of freedom, less gripping force towards irregular structures, durability reduction etc. In this work, SMAs are integrated into glass fiber reinforced fabrics with tailored properties with the help of flat-knitting technology creating an Interactive Fiber Rubber Composite by infiltrating the fabrics with liquid silicone. To determine the range of force induced, a simulation model is developed to capture the transduced force of the composite when SMA is activated and the model is calibrated with respect to a test set-up specifically tailored to determine the force exhibited. The results obtained are utilized in a future study in determining the twisting behaviour of the composite, which would further help in a better grip for small and irregular shaped objects.
Keywords: interactive fiber rubber composite; flat-knitting technology; Shape Memory Alloy; interaktywny kompozyt z włókna gumowego; technologia płaskiego dziania; stop z pamięcią kształtu